Pemanfaatan Lahan Pekarangan sebagai Pemberdayaan Masyarakat melalui Budidaya Bibit Sawo Produktif di Desa Sragi, Kabupaten Ponorogo - Wahyuni, Ajeng; Aulia Nur Azizah (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
The utilization of vacant land around the house is very important to maintain ecosystem quality and biodiversity. Plant cultivation is an effort to empower the community by optimizing the empty yard around the house. The method used is Asset Based Community Development (ABCD), where the community service program is drawn based on analysis, first appreciative findings, community mapping, social mapping, individual mapping, financial circulation and priority scale. Based on the analysis of community assets owned, the program implemented is cultivating sapodilla seeds to utilize the yard around the house. This activity consists of self-education and assistance in planting sapodilla seeds. Regular monitoring and assistance need to be done to get maximum results.